The microtubule plus end tracking protein Orbit/MAST/CLASP acts downstream of the tyrosine kinase Abl in mediating axon guidance. - Lee, H.; Engel, U.; Rusch, J.; Scherrer, S.; Sheard, K.; Van Vactor, D. (Neuron, 2004)
Axon guidance requires coordinated remodeling of actin and microtubule polymers. Using a genetic screen, we identified the microtubule-associated protein Orbit/MAST as a partner of the Abelson (Abl) tyrosine kinase. We find identical axon guidance phenotypes in orbit/MAST and Abl mutants at the midline, where the repellent Slit restricts axon crossing. Genetic interaction and epistasis assays indicate that Orbit/MAST mediates the action of Slit and its receptors, acting downstream of Abl. We find that Orbit/MAST protein localizes to Drosophila growth cones. Higher-resolution imaging of the Orbit/MAST ortholog CLASP in Xenopus growth cones suggests that this family of microtubule plus end tracking proteins identifies a subset of microtubules that probe the actin-rich peripheral growth cone domain, where guidance signals exert their initial influence on cytoskeletal organization. These and other data suggest a model where Abl acts as a central signaling node to coordinate actin and microtubule dynamics downstream of guidance receptors.